Modern Nucleophilic Aromatic Substitution - Terrier, Francois (John Wiley & Sons, Incorporated, 2013)
This book provides a comprehensive overview of nucleophilic aromatic substitutions, focusing on the mechanistic and synthetic features that govern these reactions. The first chapter presents a detailed mechanistic analysis of the factors determining the feasibility of SNAr substitutions, providing decisive information to predict regioselectivity of many reactions and to define the conditions for concerted SNAr processes. Reflecting the key role played by these species as intermediates in most SNAr reactions, chapter 2 then discusses the chemistry of anionic sigma-complexes. Chapter 3 describes the concept of superelectrophilicity in SNAr substitutions, as it has recently emerged from the reactivity of strongly electron-deficient aromatic and heteroaromatic structures. The numerous synthetic applications are considered in depth in the chapters 4 and 5 that follow on intermolecular and intramolecular nucleophilic aromatic substitutions. Then, chapter 6 focuses on substitutions proceeding formally through displacement of a hydride ion, a hot topic in the field. The final chapter brings together concise yet comprehensive discussions surrounding SNAr photosubstitutions, radical substitutions, and ANRORC substitutions. Authored by a highly respected chemist who has contributed greatly to the field over the past two decades, this is a valuable information source for all organic chemists working in academia or the pharmaceutical and agrochemical industries